2022
DOI: 10.3390/ijms23137306
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Exosomes and Intervertebral Disc Regeneration: Review

Abstract: Intervertebral disc degeneration (IVDD) is a common cause of lower back pain (LBP), which burdens individuals and society as a whole. IVDD occurs as a result of aging, mechanical trauma, lifestyle factors, and certain genetic abnormalities, leads to loss of nucleus pulposus, alteration in the composition of the extracellular matrix, excessive oxidative stress, and inflammation in the intervertebral disc. Pharmacological and surgical interventions are considered a boon for the treatment of IVDD, but the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 171 publications
0
29
0
Order By: Relevance
“…EVs, exosomes, and ncRNAs are involved in the regulation of gene expression related to ferroptosis, which has emerged as a potential therapeutic strategy for IVDD ( 116 , 145 , 146 ). The upregulation of miR-10a-5p inhibited IL-6R expression, thereby partially reducing IL-6-induced ferroptosis in chondrocytes ( 45 ).…”
Section: Ferroptosis and Ivdd Treatmentmentioning
confidence: 99%
“…EVs, exosomes, and ncRNAs are involved in the regulation of gene expression related to ferroptosis, which has emerged as a potential therapeutic strategy for IVDD ( 116 , 145 , 146 ). The upregulation of miR-10a-5p inhibited IL-6R expression, thereby partially reducing IL-6-induced ferroptosis in chondrocytes ( 45 ).…”
Section: Ferroptosis and Ivdd Treatmentmentioning
confidence: 99%
“…Compared with other cell types, MSCs can produce more exosomes through the paracrine pathway [57]. The results have shown that MSC-Exos can delay or even reverse the degenerative process of IVD by maintaining ECM homeostasis, inhibiting apoptosis of NP cells, antioxidative, and anti-inflammatory effects, although the exact underlying mechanisms have not been fully elucidated [58][59][60][61]. MSCderived exosomes (MSC-Exos) have unique advantages in the treatment of IDD when compared with MSCs.…”
Section: Application Of Endogenous and Exogenous Mscs In Thementioning
confidence: 99%
“…Bhujel B et al [ 8 ] explored whether pleiotropic effects of MSCs would be related to the differentiation capacity or mediated by the secretion of soluble paracrine factors, MSC-derived exosomes. Their extensive literature search and review clarified diverse prospects of MSC-derived exosomes to repair degenerative discs.…”
Section: Degenerative Disc Diseasementioning
confidence: 99%